Characteristics of nanostructure silicon photodiode using laser assisted etching - Ahmed, Naser M.; Yarub, Al-Douri, Assoc. Prof. Dr.; Alwan, Alwan M.; Jabbar, Allaa A.; Arif, Ghassan E. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.